Workspace Topologies of Industrial 3R Manipulators - Marco Ceccarelli; Manfred Husty; Erika Ottaviano (International Journal of Advanced Robotic Systems, 2008)
A mathematical analysis is used to characterize workspace topologies of industrial 3R manipulators. A level-set reconstruction of the workspace is formulated to identify characteristic points with fairly simple algebraic expressions. Thus, industrial 3R manipulators are classified as functions of workspace kinematic properties. Examples are illustrated to show practical usefulness of the proposed workspace characterization.